Retrieval of a separated nickel-titanium instrument and a stainless steel H-file using a novel tube, loop and file technique - Nishant Vyavahare; Meera Kulkarni; Niranjan Desai (Wolters Kluwer Medknow Publications, 2018)
Instrument separation is one of the most common procedural errors that may occur during endodontic treatment. A separated instrument can create an obstruction in the root canal which can hinder the cleaning and shaping procedures. If an instrument separation takes place, an attempt should be made to retrieve the instrument and if retrieval is not possible, the instrument should be bypassed. Nickel-titanium (NiTi) instruments have several advantages, such as superelasticity and shape memory, which prompted their use in endodontics. Due to these characteristics, NiTi instruments have shown to preserve the original anatomy and shape of the root canal. However, the disadvantage is that they fail to show signs of fatigue prior to fracture unlike stainless instruments. This article describes a case report showing the successful use of a modified tube, loop and file technique for the retrieval of two separated instruments, from a maxillary lateral incisor of a 14-year-old male patient.